Taksasi Kehilangan Hasil oleh Penyakit Kerdil pada Kentang di Jawa Tengah - Sofranita Syifa Fitriyati; Kikin Hamzah Mutaqin; Tri Asmira Damayanti (Institut Pertanian Bogor, 2020)
Potato is one of economically important crops in Indonesia. However, its production fluctuates since there are some factors affecting the yield. Recently, we found dwarf disease at potato central production area in Wonosobo and Banjarnegara Regencies in Central Java. So far, there is no information related to the yield loss caused by the dwarf disease on potato. Therefore, the research aimed to estimate the yield loss caused by the dwarf disease on potato in Central Java. The yield loss estimation was determined on some potato cultivations with different disease severities. The disease intensity was observed for five times with interval two weeks on six plots. The quantity and quality of potato yields, and selling price was calculated at the end of the observation and the correlation between the severity of disease and AUDPC (Area under disease progress curve) with yield loss was determined by regression and correlation analysis. The dwarf disease reduced plant height, individual and total tuber weight without affecting the number of tuber yield. The different of disease intensities in some area affected to the percentage of yield loss. The yield loss caused by dwarf diseases on individual potato plants up to 64.42%. Yield loss estimation caused by the dwarf disease in fields with different level of disease intensities ranged from 10.35-26.43%. Regression analysis between disease severities and yield losses showed the R square value at the level of 88.6% and a correlation at the level of 94.14%. These results indicated that the correlation between the severity of dwarf disease and yield loss is high. Keywords: disease severity, potato yield, selling price, tuber quality